Mergers in Regulated Industries: Electricity - Dennis W. Carlton (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2007)
Mergers in any industry can raise complicated questions about the elimination of competition and the achievement of efficiencies. Mergers in regulated industries such as electricity raise even more complicated issues as the analyst needs to grapple with the constraining effects of regulation, multiple levels of regulation, the ability to evade regulation, and the desire for efficiency. This paper discusses the electricity industry in general and one particular electricity merger that the U.S. Department of Justice (DOJ) recently analyzed, in order to draw several lessons about the promotion of competition through electricity mergers in the United States. The purpose is to stimulate discussion with European counterparts to see what, if anything, Europe can learn from the U.S. experience with electricity mergers and regulations.
Keywords: 330